Challenges Encountered by Teachers in the Implementation of Senior High School Curriculum - Resoor, Nonale Q. (European Journal of Applied Sciences, 2023)
The study examined and identified the challenges encountered by the teachers in the implementation of the Senior High School Curriculum and the relationship with the performance rating of teachers. The descriptive method was used with the questionnaire as the main tool in the gathering of data. The Chi-square, Pearson Product Moment Correlation, and T-test as the statistical tools used in the analysis. The findings revealed that teachers are tasked to handle subjects not within their field of specialization; Unavailability of textbooks, teachers' manuals, guides, and modules for students resulting in them spending their resources on the reproduction of these instructional materials; Students’ misuse of technology; Lack of physical facilities; Services rendered during Saturdays and holidays are not compensated with monetary benefits as these challenges were considered high extent. It was further revealed the extent of challenges encountered by senior high school teachers significantly affects their performance. Hence, Senior High School (SHS) teachers should pursue their graduate and post-graduate studies to reskill and upskill their professional and academic competencies with the recent trends in global education, in a way that will enhance their competence. In a similar direction, they are encouraged to be resourceful and innovative in the use of locally available instructional materials that will have a significant impact on the delivery of instruction. Establishing a strong partnership with the officials in government and private sectors, other community leaders, and folks in a manner that will motivate the political officialdom to lend support to schools and the stakeholders in addressing encountered issues towards quality delivery of education. Hence, there is no significant difference between the degree of challenges encountered by the respondents in the implementation of the Senior High School Curriculum when grouped and compared according to selected variables such as age, sex, civil status, and highest educational attainment.